What can evolutionary economic geography learn from global value chain and global production network research on developing and emerging economies?. Issue 2 (3rd April 2022) - Zhu, Shengjun; He, Canfei
ABSTRACT: Although evolutionary economic geography (EEG) and global production network (GPN) and global value chain (GVC) research into regional industrial restructuring and development have developed in parallel and with little mutual engagement, they provide important complementary insights. This article concentrates on what the EEG approach can learn from the GVC/GPN approach by focusing on extra-regional linkages, institutional contexts and firm heterogeneity. Analysing the role of these factors not only overcomes some weaknesses of the EEG approach but also plays an especially important role in understanding regional industrial dynamics in developing and emerging economies and in the conduct of policy-relevant research.